2007
DOI: 10.1186/1471-2148-7-180
|View full text |Cite
|
Sign up to set email alerts
|

Urodele p53 tolerates amino acid changes found in p53 variants linked to human cancer

Abstract: Background: Urodele amphibians like the axolotl are unique among vertebrates in their ability to regenerate and their resistance to develop cancers. It is unknown whether these traits are linked at the molecular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 62 publications
2
45
0
Order By: Relevance
“…Mammalian 293T cells were maintained according to established protocols and transfected with PEI (Polethylenimine; Polysciences Inc., 1 μg/μL diluted 1:1,000 in serum-free DMEM). AL1 cells (gift of Stephane Roy, University of Montreal, Montreal, Canada) were maintained and transfected according to (39). A separate stock of AL1 cells was established in galactosefree media for LacI-dependent experiments [custom gal(-) Leibovitz's L-15 media, Gibco, supplemented with 4.5 g/L glucose].…”
Section: Methodsmentioning
confidence: 99%
“…Mammalian 293T cells were maintained according to established protocols and transfected with PEI (Polethylenimine; Polysciences Inc., 1 μg/μL diluted 1:1,000 in serum-free DMEM). AL1 cells (gift of Stephane Roy, University of Montreal, Montreal, Canada) were maintained and transfected according to (39). A separate stock of AL1 cells was established in galactosefree media for LacI-dependent experiments [custom gal(-) Leibovitz's L-15 media, Gibco, supplemented with 4.5 g/L glucose].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it has been observed that inhibiting p53 disrupts limb regrowth in salamanders (19), although its role in this context has remained unknown. It is possible that p53 could play a role in the regulation of dedifferentiation and redifferentiation events intrinsic to vertebrate regeneration.…”
mentioning
confidence: 99%
“…The p53 variations associated with environmental stresses have been described in the Mexican salamander axolotl Ambystoma mexicanum and the Israeli blind subterranean mole rat (Spalax judaei; hereafter, S.j.) (7)(8)(9).…”
mentioning
confidence: 99%